2019
DOI: 10.1186/s12889-019-6804-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone consumption and Escherichia coli resistance in Japan: an ecological study

Abstract: Background The frequency of antimicrobial resistance has steadily increased worldwide, induced by inappropriate use of antibiotics in a variety of settings. We analyzed the ecological correlation between fluoroquinolone consumption and levofloxacin resistance in Escherichia coli in Japan. Methods We collected information on cases of E. coli resistant to levofloxacin in 2015–2016 in all 47 prefectures from the Japan N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
2
20
0
1
Order By: Relevance
“…However, it must be noted that a high volume of fluoroquinolone prescribing for other conditions ( 52 ) is likely to have a greater impact on fluoroquinolone resistance both in the individual and the community. Indeed, it has been shown that high fluoroquinolone use in general has been associated with an increased prevalence of resistance in E. coli over time in Eastern Asia ( 53 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that a high volume of fluoroquinolone prescribing for other conditions ( 52 ) is likely to have a greater impact on fluoroquinolone resistance both in the individual and the community. Indeed, it has been shown that high fluoroquinolone use in general has been associated with an increased prevalence of resistance in E. coli over time in Eastern Asia ( 53 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Use of quinolones confers a selection pressure that results in enrichment of a resistant subpopulation of bacteria. In line with this, use of quinolones has been linked to increased occurrence of resistant bacteria in both human and veterinary sectors (Teuber, 2001;Terahara and Nishiura, 2019). The presence of quinolone resistant E. coli (QREC) in the broiler production chain may have a public health implication, but data on these aspects are limited and the implications are therefore unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, infection risk depends on both (i) human behaviors that lead to tick bites and (ii) the risk of infection among ticks (and animals) [4749]. In the present study, we could not distinguish (i) and (ii) nor elucidate the detailed ecological mechanisms behind the observations [50]; this would require cross-disciplinary collaboration among epidemiologists and statisticians as well as entomologists, ecologists, veterinarians, and virologists.…”
Section: Discussionmentioning
confidence: 95%